Knowledge of the elderly regarding Sexually Transmitted Infections and their associated factors: an integrative review (Research, Society and Development, 2020)
Objective: The study aimed to analyze the factors associated with vulnerability to sexually transmitted infections in the elderly. Methodology: For this purpose, an integrative literature review was carried out, based on scientific articles published in the Scielo, LILACS, PubMed and Virtual Health Library databases, based on the controlled search with health descriptors: “Sexually Transmitted Diseases", "Aged" and "Primary Prevention". 08 scientific articles were included according to the criteria: documents published between 2003 and 2018; and written in Portuguese and English. Results: It was evidenced that the lack of information, the delay or neglect of diagnosis and unsafe sexual practice are elements related to the higher prevalence of sexually transmitted infections in elderly women. Conclusion: The need for more effective planning and actions is highlighted within the framework of public policies aimed at the elderly in Brazil, contemplating the binomial sexuality / health education; as well as inferring the importance of training professionals at different levels of health care about the analyzed problem